(untitled) (International Journal of Engineering and Computer Science, 2017)
Network security is a complicated subject, historically only tackled by well-trained and experienced experts. Security on the Internet and on Local Area Networks is now at the forefront of computer network related issues. With the increased number of LANs and personal computers, the Internet began to create untold numbers of security risks. A computer cluster may be a simple two-node system which just connects two personal computers, or may be a very fast supercomputer. Although a cluster may consist of just a few personal computers connected by a simple network, the cluster architecture may also be used to achieve very high levels of performance. A cluster computing security model is a scheme for specifying and enforcing security policies. This paper proposes a security model for a computer network based on cluster computing architecture by using various tools available in TCP/IP security mode